ChemInform Abstract: Intramolecular Dearomative Oxidative Coupling of Indoles: A Unified Strategy for the Total Synthesis of Indoline Alkaloids. Issue 21 (May 2015) - Zi, Weiwei; Zuo, Zhiwei; Ma, Dawei
Abstract Review: 49 refs.